2022
DOI: 10.3390/jcm11113070
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Agonist-Resistant Microprolactinoma—Mechanisms, Predictors and Management: A Case Report and Literature Review

Abstract: Objective: Prolactinomas are the most common type of functional, hormone-secreting pituitary adenomas that account for about 40% of total pituitary adenomas. Typical clinical presentations include loss of menstrual periods (amenorrhea) and galactorrhoea in women and sexual dysfunction in men. Prolactinomas are preferentially treated with dopamine agonists and respond to such therapy with hormonal normalisation and tumour shrinkage. However, about 10–20% of prolactinomas are resistant to dopamine agonists. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…After reviewing surgical notes, we found the PS texture of DA-treated tumor was mostly firm and closely adhered to the surrounding tissue, especially to the medial wall of the cavernous sinus. In contrast, other analyses have noted improved outcomes when patients were treated with bromocriptine before surgery [10,[26][27][28][29]. Whether therapy with a dopamine agonist exerts a negative effect on surgical outcome remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing surgical notes, we found the PS texture of DA-treated tumor was mostly firm and closely adhered to the surrounding tissue, especially to the medial wall of the cavernous sinus. In contrast, other analyses have noted improved outcomes when patients were treated with bromocriptine before surgery [10,[26][27][28][29]. Whether therapy with a dopamine agonist exerts a negative effect on surgical outcome remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies utilizing fMRI have consistently linked obesity to altered structure and connectivity of the central nervous system, heightened motivation to eat, and impaired self‐control and reward processes related to food (Lizarbe et al., 2020; Szmygin et al., 2023). Research has shown that food intake in obese individuals is more driven by self‐reward rather than homeostatic demands (Sewaybricker et al., 2021).…”
Section: Neuroimaging Technologies For Food Sensory and Consumer Rese...mentioning
confidence: 99%
“…Moreover, it should be noted that currently there are no generally accepted criteria for DAs-resistance [ 10 , 12 ]. Most often, it is defined as the impossibility of achieving normoprolactinemia and reducing the maximum tumor diameter by less than 50% at the maximum tolerated doses of DAs for at least 3–6 months [ 10 , 12 , 13 ].…”
Section: Dopamine Agonist Resistancementioning
confidence: 99%
“…Moreover, it should be noted that currently there are no generally accepted criteria for DAs-resistance [ 10 , 12 ]. Most often, it is defined as the impossibility of achieving normoprolactinemia and reducing the maximum tumor diameter by less than 50% at the maximum tolerated doses of DAs for at least 3–6 months [ 10 , 12 , 13 ]. The doses vary widely in different patients, but are typically ≥ 15 mg bromocriptine per day, ≥ 2.0 mg cabergoline per week, and ≥ 225 μg quinagolide per day [ 10 ].…”
Section: Dopamine Agonist Resistancementioning
confidence: 99%